Changing the Electronic Polarizability of Monolayer MoS2 by Perylene‐Based Seeding Promoters. Issue 20 (23rd August 2020) - Martella, Christian; Kozma, Erika; Tummala, Pinaka Pani; Ricci, Saverio; Patel, Kishan Ashokbhai; Andicsovà‐Eckstein, Anita; Bertini, Fabio; Scavia, Guido; Sordan, Roman; Nobili, Luca G.; Bollani, Monica; Giovanella, Umberto; et al.
Abstract: Large area molybdenum disulfide (MoS2 ) monolayers are typically obtained by using perylene‐3, 4, 9, 10‐tetracarboxylic acid tetrapotassium salt (PTAS) as organic seeding promoter in chemical vapor deposition (CVD). However, the influence of the seeding promoter and the involvement of the functional groups attached to the seed molecules on the physical properties of the MoS2 monolayer are rarely taken into account. Here, it is shown that MoS2 monolayers exhibit remarkable differences in terms of the electronic polarizability by using two representative cases of seeding promoter, namely, the commercial PTAS and a home‐made perylene‐based molecule, N, N ‐bis‐(5‐guanidil‐1‐pentanoic acid)‐perylene‐3, 4, 9, 10‐tetracarboxylic acid diimide (PTARG). By thermogravimetric analysis, it is verified that the thermal degradation of the promoters occurs differently at the CVD working condition: with a single detachment of the functional groups for PTAS and with multiple thermal events for PTARG. As a consequence, the promoter‐dependent electronic polarizability, derived by free charges trapped in the monolayer, impacts on the photoluminescence emission, as well as on the electrical performances of the monolayer channel in back‐gated field‐effect transistors. These findings suggest that the modification of the electronic polarizability, by varying the molecular promoter in a pre‐growth stage, is a path to engineer the MoS2 opto‐electronic properties. Abstract : MoS2 monolayers are obtained by chemical vapor deposition using homemade perylene‐based seeding promoters. The monolayers exhibit promoter‐dependent electronic polarizability, which impacts on the photoluminescence trion/exciton emission and on the electrical performances of back‐gated field‐effect transistors. Varying the molecular promoter in a pre‐growth stage, the MoS2 opto‐electronic properties can be engineered.